A 3D drop-size distribution model based on the convolution of raindrops at terminal velocity - Kasparis, Takis; Lane, John E.; Jones, Linwood W. (My University, 2010)
Using a matrix of drop size distributions (DSDs), measured by a microscale array of disdrometers, a method of spatial and temporal DSD interpolation is presented. The goal of this interpolation technique is to estimate the DSD above the disdrometer array as a function of three spatial coordinates, time and drop diameter. This interpolation algorithm assumes simplified drop dynamics, based on cloud advection and terminal velocity of raindrops. Once a 3D DSD has been calculated, useful quantities such as radar reflectivity Z and rainfall rate R can be computed and compared with corresponding rain gauge and weather radar data.
Keywords: Radar; Meteorological radar; Dual-polarization radar